Effects of bulk-defects and metal/bulk interface anomalies in a forming-free double-barrier memristor. (30th August 2018) - Kumar, Amitesh; Mukherjee, Shaibal; Kranti, Abhinav
Abstract: In this work, we report on a comprehensive study based on theoretical and experimental analysis to predict resistive switching in a metal-semiconductor-metal device. The impact of bulk defects (oxygen vacancies, non-lattice oxygen ions, trap charges) as bulk-limited conduction and interface anomalies (disorder-induced interface states, Schottky barrier formation/dissolution) as electrode-limited conduction for a resistive switch or memristor have been exhaustively studied. The distribution of bulk defects with applied bias which governs switching and the forming-free behavior of the device has been illustrated. Its role in the formation/dissolution of interfacial oxide is found to affect Schottky barrier considerably. The present work significantly contributes towards a further understanding and modeling of the conduction mechanisms for a wide range of resistive switches.